2017
DOI: 10.1016/j.actamat.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of microscale residual stresses in multi-phase ceramic composites using Raman spectroscopy

Abstract: A methodology is described for characterizing the spatial distribution of thermal mismatch stresses at grain level in B 4 C-SiC-Si ceramic composites using Raman spectroscopy. Unlike traditional methods to detect residual stress (e.g., X-ray diffraction) which provide average values over the entire specimen surface, Raman peak-shift analysis provides residual stress distributions within the microstructure at high spatial resolution. While the classical formulation predicts uniform compressive stress within a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The wavenumbers are functions of the boron activation level, and thus the wavenumbers are lowered considerably as the activated boron increases near the center of the silicon vein. This phenomenon of decreased wavenumbers far from grain boundaries mimics the behavior of results from Jannotti et al; however, Jannotti did not take the half‐width or asymmetry of the reported Fano profiles into account, and reported large tensile stresses in these central areas that are likely to have been an erroneous interpretation of the data. Figure displays the half‐width of the Fano profiles per the investigated points of the area scan, which qualitatively illustrates the boron activation levels of the various points.…”
Section: Resultssupporting
confidence: 76%
“…The wavenumbers are functions of the boron activation level, and thus the wavenumbers are lowered considerably as the activated boron increases near the center of the silicon vein. This phenomenon of decreased wavenumbers far from grain boundaries mimics the behavior of results from Jannotti et al; however, Jannotti did not take the half‐width or asymmetry of the reported Fano profiles into account, and reported large tensile stresses in these central areas that are likely to have been an erroneous interpretation of the data. Figure displays the half‐width of the Fano profiles per the investigated points of the area scan, which qualitatively illustrates the boron activation levels of the various points.…”
Section: Resultssupporting
confidence: 76%
“…Raman spectroscopy can be used to examine the microscopic nature of structural and/or morphological disorder, which is strongly correlated with the optical phonons in nanostructures . In the Raman spectra, the peak shifts relate to the residual stress, while the peak broadening and peak intensity decreasing reflect to structural disorder . The residual thermal stress can be determined by calculating the Raman sensitive peak shift.…”
Section: Resultsmentioning
confidence: 99%
“…The residual thermal stress can be determined by calculating the Raman sensitive peak shift. This has been employed to characterize the stress in B 4 C‐SiC‐Si composites and ZrB 2 ‐SiC composites . The Raman spectra of SiC near the interface (1‐2 μm away from the interface) were measured to investigate the residual stress near the interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations